Magnesium excretion and hypomagnesemia in pediatric renal transplant recipients. (August 2014) - Uslu Gökceoğlu, Arife; Comak, Elif; Dogan, Cagla Serpil; Koyun, Mustafa; Akbas, Halide; Akman, Sema
Abstract Background: We investigated magnesium excretion and rate of hypomagnesemia in pediatric renal transplant recipients. Method: The medical records of 114 pediatric renal transplant recipients were retrospectively evaluated. After exclusion of 23 patients, 91 patients were included in the study. We recorded serum magnesium levels at the time of measurement of urine magnesium wasting. Results: Mean serum magnesium levels were 1.73 ± 0.22 mg/dL and 38 of the patients (41%) had hypomagnesemia. There was a negative correlation between serum magnesium levels and estimated glomerular filtration rate and serum tacrolimus trough level (r = −0.215, p = 0.040 and r = −0.409, p = 0.000, respectively). Also, there was a statistically significant positive correlation between serum magnesium levels and transplantation duration (r = 0.249, p = 0.017). Mean fractional magnesium excretion was 5.9 ± 3.7% and 59 patients (65%) had high magnesium excretion. There was a significant negative correlation between fractional magnesium excretion and estimated glomerular filtration rate (r = −0.432, p = 0.001). There was a significant positive correlation between fractional magnesium excretion and serum creatinine (r = 0.379 p = 0.003). Conclusion: Patients with higher tacrolimus trough blood levels, lower glomerular filtration rate and at early posttransplant period had risk of hypomagnesemia.